The Minutes of the Meetings of the Commission of Archaeology in Vilnius: 1856–1858 - Būčys, Žygintas (Bibliotheca Lituana, 2012)
The Museum of Antiquities and Interim Commission of Archaeology in Vilnius which was the most significant educative scientific and cultural centre of that time both in Vilnius and Lithuania was founded in 1855 and was active for nearly a decade. The members of the Commission initiated and organized the research of the region in the fields of archaeology, history, and natural sciences. The Commission engaged an active part of the educated Lithuanian society in collecting the heritage of local history. Historical sources and scientific studies were also published by the Commission. The meetings of the Commission were held once a month, where past activities, current issues, and future plans were discussed as well as scientific reports were presented to the attendance. Extraordinary meetings were organized for the exceptional occasions, too. The minutes of the meetings of the Interim Commission of Archaeology in Vilnius are the source, which reflects comprehensively the activity of this public organization and its diverse character. The minutes also reflect the relationship between the Commission and the Tsarist administration: the flexibility in seeking suitable conditions for its activity, and the usage of the so-called Aesopian language in actualizing the history and the heritage of the Grand Duchy of Lithuania. The minutes reflect amply the scientific, cultural, and intellectual life of the then Lithuania. The publication presents the translated minutes of the meetings of the Interim Commission of Archaeology in Vilnius of the first three years of its activity.